Comparison of Two-Point Compression Ultrasonography Performed by Emergency Medicine Doctors and Radiologists in Detection of Deep Vein Thrombosis - Öztürk, Göknur; Selvi, Fatih; Yıldız, Günay; Atay, Süleyman; Baltacıoğlu, Bora; Bedel, Cihan (Ibnosina Journal of Medicine and Biomedical Sciences, 2023)
Introduction Venous thromboembolism (VTE) is a serious coagulation disorder that includes deep vein thrombosis (DVT) and pulmonary embolism and is an important cause of hospitalization and death. This study aimed to evaluate the compliance of the emergency doctor and radiologist in diagnosing DVT in the emergency department using the two-point compression ultrasonography (USG) method.Patients and Methods This prospective cross-sectional study was performed between February and July 2022 in the Emergency Medicine Clinic of a tertiary university hospital with patients who were thought to have DVT and had lower extremity venous USG indication. Demographic information of patients, clinical markers used in the Wells score, and USG results of the emergency doctors and radiologists were recorded in the study form.Results A total of 400 patients were included in the study. The mean age of the study patients was 59.8 ± 18.0 years, and 54.4% (n = 217) of the patients were male. There was a significant difference in the incidence of DVT between those with a Wells score of 2 or less and those above 2 (n = 67, 21.8% vs. n = 41, 47.1%; p < 0.001). Regarding interobserver agreement in the evaluation of DVT by emergency medicine doctor and radiologist, kappa values were 0.81 (95% confidence interval [CI]: 0.71–0.91) for the right femoral vein, 0.89 (95% CI: 0.81–0.97) for the left femoral vein. It was found to be 0.81 (95% CI: 0.76–0.86) for all lower extremity vein USGs.Conclusions There is a very good level of agreement between the emergency department and the radiologist in diagnosing DVT with USG.
Keywords: deep vein thrombosis; emergency medicine doctor; radiologist; two-point compression ultrasound